The Ideology of Reform and Historical Criticism of Muḥammad ʻAbduh, Aḥmad Amīn, and Sayyid Quṭb - Elnakep, Mohamed; Elgeidi, Shalabi; Branca, Paolo (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Reform is a call for renewal and modernity, therefore. Much study and refutation were attributed to it, in comparison with others, it always needs to be set and defined, that’s not for its difficulty but it’s connected to its concept with the ideologies of its advocates and their projection of its connotations and meanings on the contents of their projects and visions. For this reason, there was a dilemma among the advocates of reform in defining this concept accurately, this dilemma has dimensions that made it more obvious, by shedding light on the Ideology of reform and historical criticism of “Muḥammad ʻAbduh, Aḥmad Amīn, and Sayyid Quṭb”, we will find that their visions were for the aim of reform, the research has focused on three great thinkers with different ideologies, it started with Muḥammad ʻAbduh, one of the most prominent reformers and advocates of reform in the modern age, He contributed in liberating the Arab mind from its stagnation which inflicted it for centuries and awaken the nation’s culture awareness, reviving the Ijtihad in the intellectual and cultural aspects. Then, Aḥmad Amīn who started his journey through research and exploration of the historical, religious, and intellectual life of the Arabs, produced several historical writings that reflect his ideology in the field of reform and historical criticism. Finally, Sayyid Quṭb wrote many books, treatises, and articles that were reformist writings in various fields, including the historical field.